Pengaruh strategi 4P (Produk, Harga, Promosi, Tempat) terhadap loyalitas konsumen (studi kasus; CV. Fahri Pasuruan) - Utomo, Eko Budi; Yulandari, Putri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Consumer loyalty is an important factor that influences business competitiveness. This study aims to analyze the effect of product, price, promotion, and place on consumer loyalty at CV Fahri Pasuruan. The sample consists of 69 respondents selected using a non-probability sampling method. Data analysis was conducted using multiple linear regression with SPSS version 22. The results show that the product and price variables do not have a significant effect on consumer loyalty. In contrast, promotion and place have a positive and significant effect on consumer loyalty. Simultaneously, all four variables have a positive and significant effect on consumer loyalty, with a contribution of 46.4%. The remaining 53.6%